The epidermis and blistering disorders: pemphigus - Grando, Sergei A. (Henry Stewart Talks, 2014)
Pemphigus vulgaris (PV), PV is a life-long, life-threatening, IgG autoantibody-mediated blistering disease affecting oral/esophageal surfaces and/or skin. The fundamental myths hampered progress of pemphigus research toward development of a safe and efficient treatment. Elucidation of intimate mechanisms of keratinocyte detachment and death in pemphigus has challenged the monopathogenic explanation of disease focused of desmoglein autoimmunity. This chapter discusses recent advances of knowledge on PV, scrutinize old dogmas, resolve controversies and opens novel perspectives for treatment. PV is caused by a variety of autoantibodies that synergize with effectors of apoptotic and oncotic pathways, serine proteases, and inflammatory cytokines to overcome the natural resistance and activate the cell death program in keratinocytes. The concept of apoptolysis distinguishes the unique mechanism of autoantibody-induced keratinocyte damage in PV from other known forms of cell death. Although the optimal therapeutic strategy has not been established, the natural course of PV has improved due to a substantial progress in developing of the steroid-sparing therapies combining the immunosuppressive and direct anti-acantholytic effects. The ultimate goal pemphigus research, Cure of patients by safe, non-toxic therapy, Can be achieved through further elucidation of the molecular mechanisms mediating PV IgG-dependent keratinocyte detachment.